Relationship Between Family Support and Anxiety in High-Risk Pregnant Women in the Obgynology Clinic Permata Medika Hospital Indonesia - Sukesi, Niken; Vridayanti, Sia; Prasetyo, Ch (PT FORMOSA CENDEKIA GLOBAL, 2024)
High-risk pregnancies in pregnant women have a greater impact than normal pregnancies, including physical and psychological impacts such as worry, anxiety, fear, ambivalence, and stress. Lack of support from those closest to you can increase anxiety. Anxiety and worry in high-risk pregnant women can cause complications and long-term impacts on the mother and fetus if not treated seriously. In high-risk pregnancies, family support is crucial in lowering anxiety levels in expectant mothers. This research sought to ascertain if anxiety and family support were related in high-risk pregnant women attending the Permata Medika Hospital, Semarang's Outpatient Obstetrics Polyclinic. This study used a non-experimental with a cross-sectional approach that is included in the type of descriptive correlational research. The sample in this study was 40 respondents. Bivariate data analysis using the Spearman Rank test. The study's findings, which included a p-value of 0.001 and a rho of -0.495, show a strong, substantial, and inverse association between anxiety and family support in high-risk pregnant women at Permata Medika Hospital Semarang. At Permata Medika Hospital in Semarang, there is a connection between anxiety and family support among pregnant women with high-risk pregnancies.